DIGITALIZATION IN PUBLIC PROCUREMENT - Tkachenko, Nataliia (Socio-economic relations in the digital society, 2020)
The main electronic services and digital technologies in public procurement are considered, which are created on the basis of big data analysis and allow supervisory financial authorities and public organizations to analyze violations of funds managers, identify conflicts of interest between bidders, and assess signs of corruption. The structure of electronic platforms in the public procurement system has been investigated for the expected cost of procurement, the impact of electronic public procurement on increasing the level of competition in tenders and indicators of public procurement success. It was found that 94% of all purchases are carried out at 4 out of 20 electronic sites connected to the electronic public procurement system. The use of digital technologies has influenced the transparency of public procurement, which has doubled the level of competition in open tenders, but remains low (approximately 2.8 participants) compared to European countries, where the average level of competition is 5.4 participants. 43% of competitive supra-threshold e-procurement procedures in Ukraine are unsuccessful, of which 86% are due to lack of competition. The directions of digitalization of public procurement in Ukraine are proposed: introduction of electronic forms of such documents as tender documents, purchase agreement; narrowing points of contact in order to avoid repetition of information in templates of electronic documents; automatic warning about risk indicators of errors of bidders at the stage of procurement planning and contract execution; integration of the ProZorro IT system with the IT systems of the Ministry of Finance of the State Treasury. A model of such integration is proposed, which includes an API «Register of contracts», API «Execution of the contract», the payment calendar and information about the payment arrears in the execution of the procurement contract.